2022
DOI: 10.3390/pathogens11050539
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Valganciclovir Reduces Clinical Signs, Virus Shedding and Cell-Associated Viremia in Ponies Experimentally Infected with the Equid Herpesvirus-1 C2254 Variant

Abstract: Equid alphaherpesvirus-1 (EHV-1) is one of the main pathogens in horses, responsible for respiratory diseases, ocular diseases, abortions, neonatal foal death and neurological complications such as equine herpesvirus myeloencephalopathy (EHM). Current vaccines reduce the excretion and dissemination of the virus and, therefore, the extent of an epizooty. While their efficacy against EHV-1-induced abortion in pregnant mares and the decreased occurrence of an abortion storm in the field have been reported, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…A total of 60 experimental EHV‐1 infection studies met our inclusion criteria 24‐83 . The key characteristics of these studies are reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 60 experimental EHV‐1 infection studies met our inclusion criteria 24‐83 . The key characteristics of these studies are reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies that evaluated viremia using qPCR are shown in Figure 3B. The majority (19/23) of these studies demonstrated 100% sensitivity using this method 25,29,36,37,45,52,53,57,60,65‐67,72,73,75,77,79,80,82 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations